ANALISIS STRATEGI PENGEMBANGAN PARIWISATA (STUDI OBJEK WISATA MALINO DI DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN GOWA). - Islamiyah, Nur; Hakim, Lukman; Yusuf, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the analysis of tourism development strategies (study of Maalino tourism objects at the Tourism and Culture Office of Gows Regency. The type of research used is qualitative with a case study approach. Based on research results related to Analysis of Tourism Development Strategies (Study of Malino attractions in Gowa Regency) the following results were obtained: First, strength lies in improving the quality of the implementing apparatus through coaching and training programs so that they can carry out functions in the work structure for tourism development activities in Malini Regency, Gowa Regency, Keuda, weakness, lack of budget for the tourism office have an impact on the low quality of tourist facilities and infrastructure managed by the government of Gowa Regency.The three opportunities through events such as beautifull Malino are the government's efforts to introduce tourism objects and as an effort to open investment for tourists. a business actor in contributing to managing tourism. Fourth, the threat of damaged road infrastructure poses a threat to tourists, especially the number of cases of traffic accidents that occur. In addition, the impact of the COVID-19 outbreak has resulted in a decrease in income in tourism development activities.